2018
DOI: 10.1111/eea.12679
|View full text |Cite
|
Sign up to set email alerts
|

Promises and challenges in insect–plant interactions

Abstract: There is tremendous diversity of interactions between plants and other species. These relationships range from antagonism to mutualism. Interactions of plants with members of their ecological community can lead to a profound metabolic reconfiguration of the plants' physiology. This reconfiguration can favour beneficial organisms and deter antagonists like pathogens or herbivores. Determining the cellular and molecular dialogue between plants, microbes, and insects, and its ecological and evolutionary implicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
73
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 231 publications
(414 reference statements)
0
73
0
1
Order By: Relevance
“…As with any metric exploring patterns of biodiversity, concepts of scale are necessary to consider when examining the causes and consequences of the richness and turnover of interacting species (Giron et al 2018). Patterns observed at larger scales represent the combined processes occurring at smaller scales, but it is not always clear how patterns at nested scales relate to one another.…”
Section: Introductionmentioning
confidence: 99%
“…As with any metric exploring patterns of biodiversity, concepts of scale are necessary to consider when examining the causes and consequences of the richness and turnover of interacting species (Giron et al 2018). Patterns observed at larger scales represent the combined processes occurring at smaller scales, but it is not always clear how patterns at nested scales relate to one another.…”
Section: Introductionmentioning
confidence: 99%
“…As with any metric exploring patterns of biodiversity, concepts of scale are necessary to consider when examining the causes and consequences of the richness and turnover of interacting species (Bowman et al, 2016;Giron et al, 2018). Patterns observed at larger scales represent the combined processes occurring at smaller scales, but it is not always clear how patterns at nested scales relate to one another.…”
Section: Introductionmentioning
confidence: 99%
“…The semiochemical diversity hypothesis [SDH, (Zhang and Schlyter, 2004)] posits that mixed species forests release a complex mix of host and non-host volatiles, which can disturb olfactionguided selection of host trees by forest insect herbivores. Yet, it has been shown that the emission of plants semiochemicals can be affected by temperatures (Zhang et al, 1999;Giron et al, 2018). Tree diversity effects on resistance have been shown to vary with herbivore population density (Bognounou et al, 2017;Fernandez-Conradi et al, 2017;Merwin et al, 2017), which can be directly affected by climate or weather conditions.…”
Section: Introductionmentioning
confidence: 99%